Prediction of welding distortions and residual stresses in T-joint fillet welds by finite element method - Nguyen , Hồng Thanh; Hoang , Trọng Ánh; Nguyen , Tiến Dương; Ha , Xuân Tùng (Journal of Technical Education Science, 2016)
Fillet welds are widely used in ship building industry, automotive industry and steel structure manufacturing,… However, there exist welding distortions and residual stresses because of uneven heating and cooling. This is a factor affecting the reliability and lifetime of the welding joint. Nowadays, numerical simulation by finite element method is considered a useful tool to predict the welding deformation and residual stress right on designing. In this paper, the authors apply the software VISUAL ENVIRONMENT by ESI to modelize and simulate the welding deformation and residual stress of a T- fillet welds joint with two plates of S355J2G3 carbon steel material: the flange with the size of 310mm×200mm×5mm and the web with the size of 310mm×100mm×5mm by GMA welding. On the basis of simulation, it can be seen that when the T joint is tightly clamped by 3 directions (x, y, z) both in the flange and the web shows the minimum deformation. Simultaneously, if it is welded from two sides, the residual stress will be the minimum and there is an uneven stress distribution when it is welded in the same direction or in the opposite one.